2019
DOI: 10.3390/biomedicines7030069
|View full text |Cite
|
Sign up to set email alerts
|

Temozolomide and Other Alkylating Agents in Glioblastoma Therapy

Abstract: The alkylating agent temozolomide (TMZ) together with maximal safe bulk resection and focal radiotherapy comprises the standard treatment for glioblastoma (GB), a particularly aggressive and lethal primary brain tumor. GB affects 3.2 in 100,000 people who have an average survival time of around 14 months after presentation. Several key aspects make GB a difficult to treat disease, primarily including the high resistance of tumor cells to cell death-inducing substances or radiation and the combination of the hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
143
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(161 citation statements)
references
References 107 publications
(187 reference statements)
4
143
0
Order By: Relevance
“…It was further concluded that "TMZ should be considered primarily cytostatic and senescence-inducing and not cytotoxic and apoptosis-inducing, potentially preventing cancer cells from G2 to M phase transition when tumor cells are most sensitive for mitotic cell death." [1]. In my opinion, these are misleading and unsubstantiated statements that need comment.…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…It was further concluded that "TMZ should be considered primarily cytostatic and senescence-inducing and not cytotoxic and apoptosis-inducing, potentially preventing cancer cells from G2 to M phase transition when tumor cells are most sensitive for mitotic cell death." [1]. In my opinion, these are misleading and unsubstantiated statements that need comment.…”
mentioning
confidence: 91%
“…In a recent review in Biomedicines, Strobel et al discussed the mode of action of temozolomide, which is being used first-line in glioblastoma therapy [1]. Temozolomide (TMZ, Temodal ® ) is a spontaneously decomposing methylating agent, which acts similarly to dacarbazine (DTIC) that needs metabolic activation.…”
mentioning
confidence: 99%
“…The addition of TMZ to the standard treatment protocol was hailed as a major breakthrough in GBM therapy. Despite this, patients' prognosis remains dismal with a five-year overall survival below 10% [11]. For this reason, more efficient therapeutic approaches are required for enhancing the treatment effect [12].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the currently accepted mechanism of resistance to TMZ is the activity of O 6 -methylguanine DNA methyltransferase (MGMT), the DNA repair enzyme [6]. However, in the light of numerous TMZ effects in the cell, cannot be the only one [16].The site of TMZ action (brain) requires its effective entrance into the central nervous system (CNS) through the blood brain barrier (BBB). That is achieved with the unique chemical structure as well as pharmacokinetic properties [18,19].…”
mentioning
confidence: 99%
“…Consequently, the currently accepted mechanism of resistance to TMZ is the activity of O 6 -methylguanine DNA methyltransferase (MGMT), the DNA repair enzyme [6]. However, in the light of numerous TMZ effects in the cell, cannot be the only one [16].…”
mentioning
confidence: 99%